An analytical study of employee loyalty and corporate culture satisfaction assessment based on sentiment analysis - Xie, Jie; Su, Ri Le Ge; Song, Jaehoon (Frontiers in Psychology, 2022)
Employee loyalty and corporate culture satisfaction assessment is the core of sustainable corporate development, but most of the traditional analysis studies are based on the performance approach, using employee overtime, employee achievement and company effectiveness as data sources, the former performance data is only a side view of the company's situation, the latter as the data source of this study is a one-sided and involute form, and the data is not stable. Therefore, this paper proposes an analysis of employee loyalty and corporate culture satisfaction assessment based on sentiment analysis, using association rules and sentiment lexicons from anonymous employee evaluations to analyse the actual data.